SELF-EMPOWERMENT OF INMATES THROUGH INDEPENDENCE DEVELOPMENT AS PREPARATION FOR REINTEGRATION INTO SOCIETY AT CLASS IIA CORRECTIONAL FACILITY PEKANBARU - Andi Aldin Maharaja; Iman Santoso (Universitas Nusa Cendana, 2026)
This study analyzes the implementation of inmate self-empowerment through an independence coaching program, specifically a barista training program at the Class IIA Correctional Institution in Pekanbaru. The research focuses on how empowerment is formed and the obstacles encountered in the process, within the broader shift of Indonesia’s correctional system toward a reintegrative approach. Using a qualitative case study method, data were collected through in-depth interviews with institutional leaders, instructors, and inmate participants, supported by observation and documentation. The findings show that self-empowerment is developed through two interconnected processes. First, through social learning based on Albert Bandura’s theory, where inmates acquire barista skills through stages of attention, retention, reproduction, and motivation. Second, through the looking-glass self concept by Charles Horton Cooley, where feedback from the social environment helps reshape inmates’ self-perception from negative to more positive and confident identities. However, the empowerment process faces several challenges. Internal obstacles include low self-esteem and apathy influenced by stigma. Structural obstacles involve limited facilities, budget constraints, and the quality of instructors. External obstacles include persistent social stigma in the job market and the absence of structured post-release support or aftercare programs. In conclusion, independence coaching programs such as barista training have strong potential to foster inmate self-empowerment. However, their effectiveness depends on addressing internal psychological barriers, strengthening institutional capacity, and developing sustainable reintegration support systems after release. Keywords: Self-Empowerment; Inmates; Independence Coaching; Social Reintegration; Correctional Institution